2018
DOI: 10.1155/2018/4341961
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Investigations of the Effect of Citrus unshiu Peel Pellet on Obesity and Lipid Profile

Abstract: Objectives Several experimental studies have reported antiobesity and lipid-improving effects of Citrus unshiu. However, clinical studies on its effects are lacking. This study was designed to evaluate the impact of Citrus unshiu peel pellet (CUPP) on obesity and lipid profile. Methods For 118 patients with body mass index (BMI) > 23 who took Citrus unshiu peel pellet (CUPP) for 4 weeks in a Public Health Center, laboratory and biometric readings before and after CUPP administration were analyzed. Results Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Experimentally, several effects of CUP were proven that possesses anticancer, anti-inflammatory, anti-allergic, anti-bacterial, and anti-diabetic activities. In addition, CUP regulates hyperglycemia as well as lipid metabolism [48,49]. Kim et al reported that water extract of CUP improved cachectic symptoms in male BALB/c mice bearing CT-26 cells.…”
Section: Peel Of Citrus Unshiu Markovmentioning
confidence: 99%
“…Experimentally, several effects of CUP were proven that possesses anticancer, anti-inflammatory, anti-allergic, anti-bacterial, and anti-diabetic activities. In addition, CUP regulates hyperglycemia as well as lipid metabolism [48,49]. Kim et al reported that water extract of CUP improved cachectic symptoms in male BALB/c mice bearing CT-26 cells.…”
Section: Peel Of Citrus Unshiu Markovmentioning
confidence: 99%
“…The beneficial effects of C. pinnatifida leaves and C. unshiu peels on fat reduction and lipid metabolism have been well documented in obese animals [ 8 , 9 , 11 ]. In addition, C. unshiu peels decreased the BMIs and lowered the blood levels of total cholesterol (TC) and triglycerides (TGs) in overweight and obese adults [ 12 ]. CEMs have been shown to reduce the visceral fat and regulate the blood lipid levels in high-fat-diet-fed rodents by preventing intestinal lipid absorption; decreasing hepatic lipogenesis and gluconeogenesis; increasing hepatic β-oxidation; improving insulin sensitivity; and inhibiting adipogenesis and inflammation in adipose tissue [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bioconversion of the glycoside form of Citrus unshiu peel extract inhibited adipogenic activity by suppressing insulin‐induced protein expression and increasing adipolytic activity (Lim et al, ). Another study monitored the intake of Citrus unshiu peel pellet for 4 weeks and found that it was effective in weight control and decreased lipid profiles of subjects such as triglycerides (TG), total cholesterol (TC), and low‐density lipoprotein cholesterol (LDL‐C) level (Kang, Song, Lee, Chang, & Lee, ).…”
Section: Introductionmentioning
confidence: 99%